2008
DOI: 10.1525/auk.2008.2408.3
|View full text |Cite
|
Sign up to set email alerts
|

In Defense of Chemical Defense: Quantification of Volatile Chemicals in Feathers Is Challenging

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…those measured in auklet odorant by Hagelin et al [88]). In response, Douglas [89] argued that Hagelin et al's study underestimated the quantity of volatiles in auklet feathers because the samples were kept under suboptimal conditions, during which time they may have degraded (and see Hagelin [90]). …”
Section: Odorous Feathersmentioning
confidence: 99%
“…those measured in auklet odorant by Hagelin et al [88]). In response, Douglas [89] argued that Hagelin et al's study underestimated the quantity of volatiles in auklet feathers because the samples were kept under suboptimal conditions, during which time they may have degraded (and see Hagelin [90]). …”
Section: Odorous Feathersmentioning
confidence: 99%
“…Furthermore, fresh auklet plumage did not repel or increase morbidity of feather lice [24] and auklet ticks experimentally exposed to fresh piles of scented or unscented feathers were not repelled by scented plumage [40]. The potential role of the auklet scent thus remains questionable and would require additional experimental test (see [23, 41] for a recent discussion about this putative function of the auklet scent).…”
Section: The Role Of Olfaction In the Control Of Reproductionmentioning
confidence: 99%
“…Douglas III (2008b) suggested that the analysis of CAO upon which Hagelin and Jones (2007) based their concerns had been compromised by the loss of volatiles and the oxidation of some components of their samples, giving a distorted impression of the chemical milieu of Crested Auklet plumage. Quantifying two of the CAO constituents, Hagelin et al (2003) estimated values for the concentrations of octanal and (Z)-4-decenal in feathers from the nape at 2.98 and 1.10 lg/g, respectively.…”
Section: Auklets Wick Feathers and A Citrus-like Odourmentioning
confidence: 99%
“…Arthropod deterrents from the plumage and uropygial gland are confirmed or suspected for birds in several families, including the Alcidae (auklets) (Douglas III et al 2001, 2005a, 2005b, Douglas III 2006, 2008a, 2008b, 2013, Pachycephalidae (pitohuis) (Dumbacher 1997(Dumbacher , 1999, Parulidae (blackbirds) (Rice 2017) and Upupidae (hoopoes) (Tom as et al 2020). Although chemical defence against arthropods has been examined in few bird species, the ecological and taxonomic diversity of this assemblage suggests that the emission of arthropod deterrents from the avian integument is widespread (Mouritsen & Madsen 1994, Jønsson et al 2008) and often derived independently, even where identical compounds are involved (Dumbacher et al 2000(Dumbacher et al , 2008.…”
mentioning
confidence: 99%